Population structure and dispersal routes of an invasive parasite, Fascioloides magna, in North America and Europe. Issue 1 (December 2016) - Juhásová, Ludmila; Králová-Hromadová, Ivica; Bazsalovicsová, Eva; Minárik, Gabriel; Štefka, Jan; Mikulíček, Peter; Pálková, Lenka; Pybus, Margo
Abstract Background Fascioloides magna (Trematoda: Fasciolidae) is an important liver parasite of a wide range of free-living and domestic ruminants; it represents a remarkable species due to its large spatial distribution, invasive character, and potential to colonize new territories. The present study provides patterns of population genetic structure and admixture inF. magna across all enzootic regions in North America and natural foci in Europe, and infers migratory routes of the parasite on both continents. Methods In total, 432 individuals from five North American enzootic regions and three European foci were analysed by 11 microsatellite loci. Genetic data were evaluated by several statistical approaches: (i) the population genetic structure ofF. magna was inferred using program STRUCTURE; (ii) the genetic interrelationships between populations were analysed by PRINCIPAL COORDINATES ANALYSIS; and (iii) historical dispersal routes in North America and recent invasion routes in Europe were explored using MIGRATE. Results The analysis of dispersal routes of the parasite in North America revealed west-east and south-north lineages that partially overlapped in the central part of the continent, where different host populations historically met. The exact origin of European populations ofF. magna and their potential translocation routes were determined. Flukes from the first European focus, Italy, were related toF. magna from northern Pacific coast, while parasites from the Czech focus originated from south-eastern USA, particularly South Carolina. The Danube floodplain forests (third and still expanding focus) did not display relationship with any North American population; instead the Czech origin of the Danube population was indicated. A serial dilution of genetic diversity along the dispersion route across central and eastern Europe was observed. The results of microsatellite analyses were compared to previously acquired outputs from mitochondrial haplotype data and correlated with past human-directed translocations and natural migration of the final cervid hosts ofF. magna . Conclusions The present study revealed a complex picture of the population genetic structure and interrelationships of North American and European populations, global distribution and migratory routes ofF. magna and an origin of European foci.